2021
DOI: 10.51220/jmr.v16i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Review on Green Synthesized Nanocomposites and Their Biological Activities

Abstract: In this paper, we reviewed the present status of synthesis of nano structured materials for technological development as bimetallic, trimetallic and various organic, inorganic polymers nanocomposites in the field of nanosciences. Nanocomposites play an important role in the field of sciences, engineering and industries due to their high catalytic power, high optical, electrical and mechanical properties, which can be very useful in the field of biosensors, nano medicines and many more as social welfare factor.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Nanocomposites, especially heterocyclic ones, are considered advantageous over metallic nanoparticles as they play the role of a junction between two or more nanoparticles due to their high versatility. They have a promising position in medicinal chemistry owing to their wide spectrum of activities [ 24 ], including photosensitizer (e.g., Ag/Ti/Zn Trimetallic Nanoparticles and Carbon Quantum Dots Nanocomposites) [ 25 ], antimicrobial [ 26 ], and antioxidant activity (e.g., bio-Ag/CdO/ZnO@MWCNTs nanocomposites) [ 27 ], by using several different methods. For antibacterial activities, zinc- and copper-doped TiO 2 nanoparticles have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites, especially heterocyclic ones, are considered advantageous over metallic nanoparticles as they play the role of a junction between two or more nanoparticles due to their high versatility. They have a promising position in medicinal chemistry owing to their wide spectrum of activities [ 24 ], including photosensitizer (e.g., Ag/Ti/Zn Trimetallic Nanoparticles and Carbon Quantum Dots Nanocomposites) [ 25 ], antimicrobial [ 26 ], and antioxidant activity (e.g., bio-Ag/CdO/ZnO@MWCNTs nanocomposites) [ 27 ], by using several different methods. For antibacterial activities, zinc- and copper-doped TiO 2 nanoparticles have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Ripe V. floribudum fruits possess properties of interest for different industries, such as for the synthesis of photocatalytic nanocomposite materials (Vizuete et al, 2016). Anthocyanin molecules in fruits of V. floribundum and other Vaccinium species have hydroxyl groups that effectively bind with TiO 2 nanoparticles, which are important for the nanoparticle industry (Taco-Ugsha et al, 2020;Ringwal et al, 2021).…”
Section: Agracejo Vaccinium Floribundum Kunthmentioning
confidence: 99%
“…suspensions were removed from the reactor, centrifuged at 10min intervals, and their distinctive absorption spectra were recorded using de-ionized water as a reference on a UV-vis spectrophotometer [25][26][27][28][29][30]33] . The concentrations of the dyes were calculated using calibration curves.…”
Section: Determination Of Catalytic Activitymentioning
confidence: 99%
“…To confirmation of AgNPs formation, EDAX was performed, in which a strong peak of elemental Ag (69.14 weight %) and other peaks of O (22.24 weight %) and C (8.62 weight %) elements were present. The synthesized powdered sample of nano material additionally used for TEM analysis in which it was observed that the green AgNPs were polydispersed, smooth morphology and irregular shaped grains having average size of 43.75nm [12,[18][19][31][32][33][34][35][36] . BET isotherm plot (see Figure .2) of synthesized sample revealed that the synthesized AgNPs have single point surface area (SPSA at P/Po) was 0.1398 m 2 /gm, BET surface area was 0.1057 m 2 /gm, Langmuir surface area (LSA) was 0.1465m 2 /gm, and the micro pore area was 0.7834 m 2 /gm [28] , on the basis of observed data due to which it may become a corrosion free material and may use as a good anti-corrosion material as well as protecting material.…”
Section: Characterization Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation